Dietary alpha‐ketoglutarate promotes beige adipogenesis and prevents obesity in middle‐aged mice - Tian, Qiyu (Aging Cell, 2019)
Aging usually involves the progressive development of certain illnesses, including diabetes and obesity. Due to incapacity to form new white adipocytes, adipose expansion in aged mice primarily depends on adipocyte hypertrophy, which induces metabolic dysfunction. On the other hand, brown adipose tissue burns fatty acids, preventing ectopic lipid accumulation and metabolic diseases. However, the capacity of brown/beige adipogenesis declines inevitably during the aging process. Previously, we reported that DNA demethylation in the Prdm16 promoter is required for beige adipogenesis. DNA methylation is mediated by ten–eleven family proteins (TET) using alpha‐ketoglutarate (AKG) as a cofactor. Here, we demonstrated that the circulatory AKG concentration was reduced in middle‐aged mice (10‐month‐old) compared with young mice (2‐month‐old). Through AKG administration replenishing the AKG pool, aged mice were associated with the lower body weight gain and fat mass, and improved glucose tolerance after challenged with high‐fat diet (HFD). These metabolic changes are accompanied by increased expression of brown adipose genes and proteins in inguinal adipose tissue. Cold‐induced brown/beige adipogenesis was impeded in HFD mice, whereas AKG rescued the impairment of beige adipocyte functionality in middle‐aged mice. Besides, AKG administration up‐regulated Prdm16 expression, which was correlated with an increase of DNA demethylation in the Prdm16 promoter. In summary, AKG supplementation promotes beige adipogenesis and alleviates HFD‐induced obesity in middle‐aged mice, which is associated with enhanced DNA demethylation of the Prdm16 gene.